Embracing the employee orientation: does customer relationship matter in brand building?. Issue 2 (10th June 2021) - Jhamb, Deepika; Kampani, Nidhi; Arya, Vikas
Abstract : Purpose: The study aims to explore the themes responsible for employee orientation and further their role in building strong customer relationships in telecom and organized retail outlets in emerging markets. Design/methodology/approach: Employing the qualitative approach, a total of 31 in-depth interviews with customer relationship management (CRM) officers of telecom and organized outlets were carried out. Data were analysed using NVIVO-12 plus and ATLAS tools. Findings: The analysis extracted 13 unique themes namely training and development, communication skills, convincing skills, interpersonal skills, knowledge management, grievance handling, organisation's culture development, service climate, adaptive behaviour, customer retention skills, customer profiling, trust and commitment, and suitability of employees. The results claimed that these themes can assist in building strong customer relationships. However, the extent of the significance of themes may vary for telecom and organized retail outlets. Research limitations/implications: The findings have vital implications for frontline employees to drive customer value as they directly involve with customers. Findings further suggest that hiring of employees according to their location and catchment area of outlets are utmost important. Originality/value: Employee orientation is an indispensable determinant in building a sustainable relationship with customers through uniqueness and consistency in meeting customers' expectations. This is a first attempt to explore the various unique themes responsible for employee orientation and the imperative role of such themes in maintaining long-lasting customer relationships.